Predicting joint destruction in rheumatoid arthritis with power Doppler, anti-citrullinated peptide antibody, and joint swelling. Issue 6 (8th September 2015) - Kirino, Yohei; Hama, Maasa; Takase-Minegishi, Kaoru; Kunishita, Yosuke; Kishimoto, Daiga; Yoshimi, Ryusuke; Asami, Yukiko; Ihata, Atsushi; Oba, Mari S.; Tsunoda, Shinichiro; Ohno, Shigeru; Ueda, Atsuhisa; et al.
Abstract : Objective. To determine combined evaluation of musculoskeletal ultrasonography (MSUS) and power Doppler (PD) signals, anti-citrullinated peptide antibody (ACPA), and other clinical findings improve the prediction of joint destruction in rheumatoid arthritis (RA). Methods. We performed a retrospective study of 331 RA patients (female n = 280 and male n = 51, mean age: 57.9 ± 13.2 years) who underwent MSUS from 2002 to 2012. Correlations with progression of joint destructions in 1, 308 2nd and 3rd metacarpophalangeal (MCP) joints and various factors including PD signals of the same joints, clinical findings, age, disease duration at the study entry, gender, observation period, radiographic bone scores according to modified Sharp–van der Heijde methods, ACPA, and rheumatoid factor (RF) were analyzed in patient- and joint-based fashions, using univariate and multivariate logistic regression analyses and generalized linear mixed model. Results. Patients' characteristics were as follows: mean disease duration: 5.7 ± 7.5 years, observation period: 4.6 ± 2.6 years, RF positivity: 79.9%, and ACPA positivity: 77.5%. PD-positive 2nd and 3rd joints showed higher rate of joint destruction, especially in ACPA-positive patients. Moreover, PD-positive joints in ACPA-positive patients showed joint destruction even in joints without swelling. Multivariate analysis determined PD, swollen joint (SJ), observation period, basal radiographic bone scores, and ACPA as independent risks for joint destruction. Conclusion. PD, SJ, basal radiographic bone scores, and ACPA are independent predictors for the joint destruction of 2nd and 3rd MCPs in RA; thus, considering these factors would be useful in daily practice.